Pengaruh Media Sosial dan Brand Ambassador Terhadap Minat Beli Konsumen Pada Produk Wardah di Jakarta Pusat - Nurseno, Bertadi; Luthfi, Alaika Putri Nafa'ni (JAMBIS : Jurnal Administrasi Bisnis, 2025)
This research aims to determine the influence of Social Media and Brand Ambassador on Purchase Intention for Wardah products in Central Jakarta. The research method employed is Non-probability Sampling, specifically using Convenience/Accidental Sampling, with 100 respondents. Data collection was conducted through questionnaires distributed to respondents via social media using Google Forms. The instrument testing techniques used include Validity and Reliability tests. Data analysis methods include Classical Assumption tests, Multiple Linear Regression Analysis, ttests, f-tests, and the Coefficient of Determination. The results indicate that Social Media (X1) significantly influences Consumer Purchase Intention (Y) for Wardah brand products. Additionally, Brand Ambassador (X2) significantly affects Consumer Purchase Intention (Y) for Wardah brand products.